Identification and characterization of phosphoproteins in the striated and smooth adductor muscles of Yesso scallop Patinopecten yessoensis. (15th March 2022) - Sun, Xiujun; Li, Li; Zhang, Tianshi; Chen, Limei; Zheng, Yanxin; Zhou, Liqing; Wu, Biao; Liu, Zhihong
Highlights: Muscle fiber area and density in scallops is in relation to texture parameters of the striated and smooth adductor muscles. A total of 743 different phosphoproteins have been revealed between the striated and smooth adductor muscles. The unique phosphorylation sites of glycolytic enzymes have been identified in the striated adductor muscle. The findings will provide new evidences on the role of muscle structure and protein phosphorylation in scallop meat quality. Abstract: Many proteins are known to be phosphorylated, affecting important regulatory factors of muscle quality in the aquatic animals. The striated and smooth adductor muscles of Yesso scallop Patinopecten yessoensis were used to investigate muscle texture and identify phosphoproteins by histological methods and phosphoproteomic analysis. Our present study reveals that muscle fiber density is in relation to meat texture of the striated and smooth adductor muscles. The phosphoproteomic analysis has identified 764 down-regulated and 569 up-regulated phosphosites on 743 phosphoproteins in the smooth muscle compared to the striated part. The identification of unique phosphorylation sites in glycolytic enzymes may increase the activity of glycolytic enzymes and the rate of glycolysis in the striated adductor muscle. The present findings will provide new evidences on the role of muscle structure and protein phosphorylation in scallop muscle quality and thus help to develop strategies for improving meat quality of scallop products.